Transformative change for a sustainable management of global commons: Biodiversity, forests and the ocean. Recommendations for international cooperation based on a review of global assessment reports and project experience - Heidi Wittmer; Augustin Berghöfer; Leonie Büttner; Ruchira Chakrabarty; Johannes Förster; Sabina Khan; Claudia König; Gesche Krause; David Kreuer; Karla Estela Locher Krause; Thais Moreno Soares; Marcela Mu\~noz Escobar; et al. (Helmholtz-Zentrum für Umweltforschung (UFZ), 2021)
Global scientific assessments increasingly reach the conclusion that transformative change of global production and consumption systems is necessary to safeguard and maintain global commons, such as biodiversity, natural forests and the ocean, and to stabilise climate at the global scale. Against this background the present study analyses the conclusions of global assessments and derives recommendations on how to increase the transformative potential of international negotiations and agreements as well as development cooperation programs, projects, and initiatives. The study develops a conceptual framework building on the academic literature and argues that interventions are much more likely to achieve transformation to sustainability if they are embedded within a more comprehensive framing of transformative change consisting of 1. a compelling transformative vision, 2. knowledge on systemic change, 3. navigation of the dynamics inherent in changing development pathways, and 4. emancipated agency providing room for inclusive deliberation and 5. combine transformative modes of governance. The study identifies core challenges and gaps for the conservation and sustainable management of biodiversity in general and for forests and the ocean by (i) examining the recommendations from global assessments and reports on the state of nature and the environment, and (ii) by analysing international cooperation projects for biodiversity, forests and the ocean with regard to their transformative potential. Finally, the study provides recommendations on how Germany can support transformation in the context of international and development cooperation.
Keywords: 330; sustainable development; biodiversity; forests; the ocean; ecosystems; transformative change; SDGs; sustainability goals; global assessments; global commons; sustainability transformation; policy measures; German Development cooperation; governance